Learning Path : Understanding Cognitive Biases - Alvarez, Cindy (O'Reilly Media, Inc., 2017)
Cognitive biases can unconsciously cause product people to make product mistakes and lead customers to make baffling purchasing decisions. In this Learning Path, you'll gain a deep understanding of how cognitive bias works in the human brain and learn to recognize seven different forms of cognitive bias: hindsight bias, cognitive dissonance, confirmation bias, choice-supportive bias, social desirability bias, projection bias, and anchoring. By understanding these brain processes, you'll know what triggers cognitive biases, how to counteract their effects, how to avoid product mistakes, and learn to build better products.